Emotional Intelligence in Voice Assistants : Advancing Human-AI Interaction - Ankur Binwal, (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2024)
This article explores the integration of emotional intelligence (EI) into AI voice assistants, examining techniques for emotion recognition from speech, adaptive response generation, and the impact on user experience. It discusses key components including acoustic feature analysis, machine learning approaches, and multimodal systems for emotion detection. The article also addresses ethical considerations such as privacy concerns, potential manipulation, and technical challenges in achieving robust, real-time, and culturally-adaptive EI systems. Applications in mental health support and customer service are examined, highlighting both the potential benefits and necessary precautions. Through a comprehensive review of recent research, this work aims to contribute to the responsible development of emotionally intelligent AI voice assistants that enhance human-AI interaction while prioritizing user well-being.
Keywords: Emotional Intelligence; Voice Assistants; Human-AI Interaction; Speech Emotion Recognition; Ethical Considerations